La intervención social con la exclusión. Una mirada desde el mundo de los incluidos - Malagón, Santos (Cuadernos de Trabajo Social, 2007)
This article critically reviews the panorama of social intervention with socially excluded persons. This observation’s perspective comes from experience with work done in the context of non-profit social entities. It seeks to reflect upon the social representations that we all hold within ourselves, consciously or not, which spring from our social origins and which filter our world concept and, as such, our work.